Sistem Informasi Fotografi Berbasis Website Menggunakan Metode Agile - Ikhsan, Muhammad; Praptiwi, Riska Amalia; Jamaluddin, Bunga Mawar; Salsabilah, Hanum; Akbar, Andi Muh; Khaidir, Khaidir (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
Photography service users often face difficulties in accessing effective and efficient photography services through digital platforms. This study aims to develop a web-based photography information system using the Agile method, which allows for rapid adaptation to user needs and market changes through continuous iterations. The development results indicate that the system can effectively provide key features such as account registration, login, dashboard, photographer services, and photography equipment rental. Functional and non-functional testing ensures that the system operates well and meets user needs. However, there are challenges in optimizing security features and response times that need to be addressed in the next iteration. The system has been successfully developed and is capable of providing better services to users, although further improvements are needed in some technical aspects.